MEANING SHIFTS IN THE LYRICS OF TRANSLATED SONGS "EUREKA MILIK KITA" AND "SEVENTEEN" BY JKT48 - Rawdhotunnimah, Silmi; Ali, Mohammad (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
This study aims to describe the shift of meaning in the lyrics of the translated songs Eureka milik kita and Seventeen by JKT48 based on the theory proposed by Vinay and Darbelnet (1965). The data source is taken from 2 songs in JKT48's Mahagita Vol.2 album which was released in October 2023 by Producer Akimoto Yasushi under the ownership of PT Indonesia Musik Nusantara by using qualitative descriptive research methods and note taking techniques. A deep understanding of meaning shifts in the translation process is important to improve the quality of cross-cultural communication and minimize the risk of misunderstanding. The results obtained are that overall there are 16 shifts in meaning. Of the 16 shifts, there are 7 modulations of meaning coverage, 1 modulation of viewpoint, 5 additions, and 3 deletions. In the song Eurika Milik Kita, there is no shift in the meaning of the Modulation of Viewpoint.